Analysis of the RSG-GAS PPF Value Dependence on the Fuel Burnup - Suparlina, Lily; Purwadi, Purwadi; Kunihiko, Nabeshima (Jurnal Teknologi Reaktor Nuklir Tri Dasa Mega, 2022)
The RSG-GAS reactor has been operated in a safe and reliable manner for about 35 years since it commenced its operation in 1987 to serve radioisotopes production, NAA, neutron beam experiments, material irradiation, and reactor physics experimental activities as well as training purposes. Power peaking factor (PPF) has a strong relation to operation safety as well as service availability. Its value is necessary to determine by calculation since it is impossible to determine it experimentally in the core. This paper is intended to analyze the PPF values of the RSG-GAS reactor core as a function of burnup. The analysis was done using WIMSD-5B/BATAN-3DIFF computer codes. The result shows that the PPF values are significantly different for each burnup or energy in MWD. The values of axial and radial PPF are still under the safety limit and the BATAN-3DIFF code satisfyingly determines the PPF values of the RSG-GAS reactor core and supports the safety of reactor operation.